Determine the Outcome of Newborn in Post-Term Pregnancy (Medical Forum Monthly, 2024)
Objective: To assess the outcome of newborn among pregnant females who deliver after prolonged pregnancy.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Islam Central Hospital, Sialkot from October 2018 to March 2019.Materials and Methods: One hundred patients with pregnancy of 42 weeks or above were included. Patients with medical disorders, intrauterine demise or pregnancy complications were excluded. Identification of parameters regarding poor neonatal outcome was done. Gestational age, parity, fetal movement, age, mode of delivery, ultrasound, admission cardiotocogram (CTG) and past prolonged pregnancy were recorded.Results: There were 39 (39%) between 20-25 years of age. Multigravida was found in 60 (60%) and emergency caesarean section 65 (65%). Most of the babies 64% were admitted to neonatal intensive care unit (ICU). Complication of meconium aspiration syndrome was found 67 (67%). No fetal mortality was observed.Conclusion: Pregnancy should be managed before 42 weeks of gestation and should not allow to went post-term due to high rate of neonatal mortality and morbidity.